نمذجة الحساب الحراري والموازنة الحرارية لمحرك بنزين بشحن طبيعي وشحن قسري باستخدام برنامج اﻠ Matlab - سعيد, مي (Latakia University Journal -Engineering Sciences Series, 2018)
The internal combustion engines consider the most of thermal engines spread, because of solidarity and durability and economical of those engines and long age, they are used in wide and different scopes, and they consider the main source of energy in the building machinery and the transport, some ships move by gas turbines and planes by jet engines. we must distinguish between the engines by natural charging by absorbing or supercharging by compressor, that according to the conditions of exploitation this or that engine. for the great development in the scope of the design and using the computer in the design process as a method which is achieved the speed in design and accuracy in the performance, The researcher has prepared programming pattern by using Matlab program for thermal calculation and balancing for the petrol engine by natural charging and supercharging, and the researcher has calculated performance pointers and drawn performance curves, and has compared between the results to find the optimal solution which ensure high energy of engine and less of the fuel consumption, therefore the pollution which is produced from it reduces. تعتبر محركات الاحتراق الداخلي من أكثر المحركات الحرارية انتشاراً، حيث بفضل تماسك ومتانة واقتصادية هذه المحركات، وعمرها المديد فإنها تستخدم في مجالات واسعة ومختلفة، كما أنها تعتبر المصدر الرئيس للطاقة في آلات البناء ووسائط النقل، بعض السفن يتم تحريكها بعنفات غازية وكذلك الطائرات بمحركات نفّاثة. لا بد من تمييز المحركات من حيث الشحن الطبيعي للمحرك بالامتصاص، أو الشحن القسري بواسطة ضاغط وذلك طبقا لظروف استثمار هذا أو ذاك المحرك. نظراً للتطور الهائل في مجال التصميم واستخدام الحاسوب في عملية التصميم كوسيلة تحقق سرعة في التصميم ودقة في الأداء، فقد قام الباحث بإعداد نموذج حاسوبي باستخدام لغة اﻠ Matlabللحساب الحراري والموازنة الحرارية لمحرك بنزين بشحن طبيعي وشحن قسري، كما تم حساب مؤشرات الأداء للمحرك ورسم منحنيات الأداء، والمقارنة بين النتائج وذلك لاستنباط الحل الأمثل الذي يضمن استطاعة عالية للمحرك ومصروف أقل للوقود وبالتالي انخفاض التلوث الناتج عنه.